Algorithms of motion in the particle-in-cell method - Voropaeva, Ekaterina S.; Vshivkov, Konstantin V.; Vshivkova, Lyudmila V.; Dudnikova, Galina I.; Efimova , Anna A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2021)
in electromagnetic fields and compares this method with various known modifications of the Boris method. The created two-dimensional and three-dimensional algorithms are based on the use of an exact solution of the differential equation for the velocity of a charged particle at a time step. A comparative analysis of the Boris method and its modifications was carried out both in terms of the accuracy of the methods and the time of their operation. A new modification of the Boris method allows more accurate calculations of the trajectory and velocity of a charged particle without a significant increase in the complexity of calculations. It is shown that, when choosing a modification of the Boris method to solve a problem, one should pay attention first of all to the accuracy of the solution, since a simpler and faster scheme may not give a gain in time.